Answer: 25 and 22
Step-by-step explanation:
Since one number is 3 bigger than the other, we can call them x, and x-3.
Then we know that the sum of 3 times x and 2 times (x-3) is equal to 19, so we can make the equation
3x+2(x-3)=19
Simplifying would get you
3x+2x-6=19
adding the x's and adding six to both sides of the equations gets you
5x = 25
divide by 5 and
x=5
Put those numbers back into your previous labels for them, x and x-3, and you get 5 and 2
Hope this helps
Answer:
f(g(2)) = 22
General Formulas and Concepts:
<u>Pre-Algebra</u>
- Order of Operations: BPEMDAS
<u>Algebra I</u>
Step-by-step explanation:
<u>Step 1: Define</u>
f(x) = 3x + 1
g(x) = 2x² - 1
<u>Step 2: Find g(2)</u>
- Substitute: g(2) = 2(2)² - 1
- Evaluate: g(2) = 2(4) - 1
- Multiply: g(2) = 8 - 1
- Subtract: g(2) = 7
<u>Step 3: Find f(g(2))</u>
- Define: g(2) = 7
- Rewrite: f(7)
- Substitute: f(7) = 3(7) + 1
- Multiply: f(7) = 21 + 1
- Add: f(7) = 22
And we have our final answer!
C= (31+7)1/2
Carlos has 19 points
double check
19•2 = 38-7 = 31
Answer:
9.49
Step-by-step explanation:
Divide 47.45 by five to find the answer.